Study the effect of annealing temperature on the electron transitions of SnO 2 films. doped with (Ag 2 O) prepared by precipitation Thermal chemical (Journal of the College of Basic Education, 2023)
Thin Ag 2 O doped SnO 2 films and SnO 2 films were prepared.by weight (3%, 5%) using the thermal chemical deposition method on bases ofBorosilicate glass at a temperature (500 ºC).The X-ray diffraction pattern of the films prepared at different temperatures was studied.annealing (540, 580, 620) ºC, as the results of x-ray diffraction showed thatThe membranes have a polycrystalline structure.The study included the effect of annealing temperature on the forbidden energy gap of transitions.direct electronic, as it was found that an increase in the annealing temperature caused a decrease in the gapbanned energy.